Pluchea indica metabolites production under chicken manure application in the rainy season - Haya Azharul Jinan; Sandra Arifin Aziz; Maya Melati; Youngkwan Cho; Yulia Rahmah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2026)
Indian camphorweed (Pluchea indica), an indigenous vegetable, has promising potential as a cosmetic raw material because of its bioactive compounds. Research on cultivation techniques is relatively underexplored in agronomic research, particularly in fertilization practices for P. indica in the rainy season, a period that is critical for tropical agriculture. This study aimed to determine the optimal chicken manure dosage for the growth and yield of four-month-old Indian camphorweed during the rainy season. The experiment was conducted at IPB University, Indonesia, from November 2023 to February 2024. A randomized complete block design (RCBD) was applied, consisting of four chicken manure dosages: 0, 2.5, 5.0, and 7.5 kg per plant, with three replications. Results showed that chicken manure application was found to enhance vegetative growth, branching, leaf yield, and leaf N and K status, indicating its suitability as an organic nutrient source under high-rainfall conditions. Regression analysis indicated the optimal dosage of chicken manure was 7.00 kg per plant for fresh weight yield at 27 weeks after planting (WAP). Chicken manure application changes the phenolic content and antioxidant capacity, that suggest the trade-offs between yield improvement and certain aspects of functional quality. Keywords: Indian camphorweed; optimum dosage; organic fertilizer